Meckel's Diverticulitis Causing Acute Intestinal Obstruction in Rural Area: a Rare Case Report (JBN (Jurnal Bedah Nasional), 2025)
Aim: To study acute intestinal obstruction as complication of Meckel’s diverticulitis in rural area. Case Presentation: A 13-year-old boy presented with diffuse abdominal pain, nausea, vomiting, and abdominal distension persisting for four days. The abdominal X-ray revealed dilated bowel loops and air-fluid levels, indicating obstruction. During exploratory laparotomy, a mesodiverticular band compressing the ileum was identified, along with a perforated Meckel’s diverticulum approximately 100 cm proximal to the ileocecal junction. The trapped intestinal loop was released, and the diverticulum was resected. The procedure included peritoneal lavage and drain placement. The patient was closely monitored postoperatively, with further management tailored according to clinical progress and histopathological findings. Conclusion: This case underscores the importance of early diagnosis and individualized surgical strategies in complicated Meckel’s diverticulum, particularly in resource-limited settings. Open laparotomy remains the preferred method for severe cases involving perforation or obstruction